Exploring the Impact of the Metaphorical Concepts of As-Sirāt on the Architectural Structure of Allahverdi Khan Bridge - Payandeh, Mehrsa; Hariri, Azadeh; Hakim, Negar (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
Some Islamic theological resources provide descriptions of the afterlife, with particular attention to architectural elements such as the As-Sirāt bridge. This bridge is a significant concept in Islamic theology, depicted as a pathway extending over Hell. Islamic hadiths and literature offer various interpretations of this bridge. During the Safavid era, architects frequently employed symbolism, especially through the use of numbers and strategic location choices, to embed Islamic concepts into their designs, thereby connecting form and meaning in their architectural works. Similarly, the architecture of bridges in Iran reflects the integration of form and meaning, as well as the expression of Islamic ideas. Utilizing a descriptive-analytical approach and drawing on field and library research, this study examines how the metaphorical concepts associated with the As-Sirāt Bridge influenced both the design and location of the Allahverdi Khan Bridge. The findings indicate that the metaphorical concepts of the As-Sirāt Bridge significantly impacted the placement of the Allahverdi Khan Bridge and its use of numerical symbolism in the design of its gates.